Properties 0-3 PZT-Portland cement composites - N. Jaitanong (2018)
Smart structural composites are multifunctional structural materials which can perform functions such as sensing strain, vibration reduction and are essential because of their relevance to mitigation and structural vibration control. Cement-based piezoelectric composites have been developed as smart structural composites. The goal of this work is to produce cement-based piezoelectric composites using lead zirconate titanate (PZT) and Portland cement (PC) with xPZT-(1 - x)PC (where x = 0.3, 0.6 and 0.9). The composites were pressed together and cured in 100% RH curing chamber for 3 days before measurements. Dielectric constant (εr) at room temperature and piezoelectric coefficient (d33) of the 0-3 piezoelectric PZT-Portland cement composites with different PZT content were investigated. The results show these composites have εr and d33 values of up to 536 and 87 pC/N, respectively, and there is a good potential for the application of these cement-based piezoelectric composites in civil engineering. © 2007 Elsevier Ltd and Techna Group S.r.l.